Effects of compound-specific transverse mixing on steady-state reactive plumes: Insights from pore-scale simulations and Darcy-scale experiments - Hochstetler, David L.; Rolle, Massimo; Chiogna, Gabriele; Haberer, Christina M.; Grathwohl, Peter; Kitanidis, Peter K. (Advances in Water Resources, 2013)
Transverse mixing is critical for reactions in porous media and recent studies have shown that to characterize such mixing at the Darcy scale a nonlinear compound-specific parameterization of transverse dispersion is necessary. We investigate the effectiveness of this description of transverse mixing in predicting reactive transport. We perform pore-scale numerical simulations and flow-through laboratory experiments to study mixing-limited reactions with continuous injection of reactants that result in steady-state reactive plumes. We consider product mass flux and reactant plume lengths as metrics of reactive transport. This study shows that the nonlinear parameterization of transverse dispersion consistently predicts both product mass flux and reactant plume extents across two orders of magnitude of mean flow velocities. In contrast, the classical linear parameterization of transverse dispersion, assuming a constant dispersivity as a property of the porous medium, could not consistently predict either indicator with great accuracy. Furthermore, the linear parameterization of transverse dispersion predicts an asymptotic (constant) plume length with increasing velocity while the nonlinear parameterization indicates that the plume length increases with the square root of the velocity. Both the pore-scale model simulations and the laboratory experiments of mixing-limited reactive transport show the latter relationship. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Compound-specific transverse dispersion; Dilution index; Mixing; Plume length; Pore-scale modeling; Reactive transport